Questioning Popular Culture: Future Technology In Ready Player One - Muhammad Iman Rafif; Achmad Munjid (Universitas Gadjah Mada, 2021)
This study investigates the impact of future technology products, as one of the parts of popular culture, on society in the science fiction novel Ready Player One by Ernest Cline (2011) and on our current society. The primary data of this study were taken from the novel. The results reveal that the effects of popular culture, specifically the products of technology, on modern society are enormous compared to the society in the novel. The similarities and differences between the technological aspects portrayed in the story compared to the current modern world are revealed to know what really happens and going to happen in the future.